2023
DOI: 10.1002/admt.202300079
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible Strain Sensor with High Electrical Conductivity, Rapid Electrothermal Response, and High Strain Sensitivity for Real‐Time Monitoring of Human Joint Movement

Abstract: Here, a flexible film, called PPA film, is designed as a multifunctional sensor with high electrical conductivity, rapid electrothermal response, and high strain sensitivity. The film contains polyvinyl alcohol (PVA), graphene nanosheets (GNs), nanocellulose crystals (CNCs), polydopamine (PDA), and silver nanoparticles (Ag NPs), symbolized as PPA film. The CNCs enhance the dispersion of the GNs during film formation; the stacked GNs change heat conduction and resistance during film bending; PDA serves as a lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The results of this study were compared with those of flexible polymer substrates such as PVA, PI, and PET, widely used in strain sensor production. Figure 9 represents the performance indicator comparison of reported the gauge factor and strain level of graphene-based polymer by He et al, 66 Li et al, 67 Liu et al, 68 Lynch et al, 69 and Htwe et al 70 As shown in Figure 9, graphene/AgNPs spray-coated PVA/GO/BHET strain sensors possess remarkable sensitivity at a very low strain level of 0.04%.…”
Section: Literature Comparison and Suggestionsmentioning
confidence: 99%
“…The results of this study were compared with those of flexible polymer substrates such as PVA, PI, and PET, widely used in strain sensor production. Figure 9 represents the performance indicator comparison of reported the gauge factor and strain level of graphene-based polymer by He et al, 66 Li et al, 67 Liu et al, 68 Lynch et al, 69 and Htwe et al 70 As shown in Figure 9, graphene/AgNPs spray-coated PVA/GO/BHET strain sensors possess remarkable sensitivity at a very low strain level of 0.04%.…”
Section: Literature Comparison and Suggestionsmentioning
confidence: 99%
“…91,92 Paper is a favorable substrate to manufacture POC in-vitro diagnostic devices due to its abundant availability, affordability, chemical stability, biodegradability, prominent porous fibrous network with high surface area for interactions, and natural capillary-driven mass transport of liquid samples. 93–97 Various well-established technologies for the manufacture and processing of paper have been applied for the fabrication of paper-based microfluidic devices, including folding, cutting, 98,99 masking, 100,101 laser writing, 102 and printing. 103–105 However, paper can vary immensely based on its composition, internal structure, and wettability owing to its sources and manufacturing method, 106 for example, filter paper, 107,108 chromatography paper, 109 common printer paper, 110 and paper towels.…”
Section: Paper-based Biosensorsmentioning
confidence: 99%